2016
DOI: 10.1016/j.ultsonch.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound induced green solvent extraction of oil from oleaginous seeds

Abstract: Ultrasound-assisted extraction of rapeseed oil was investigated and compared with conventional extraction for energy efficiency, throughput time, extraction yield, cleanness, processing cost and product quality. A multivariate study enabled us to define optimal parameters (7.7 W/cm(2) for ultrasonic power intensity, 40 °C for processing temperature, and a solid/liquid ratio of 1/15) for ultrasound-assisted extraction of oil from oilseeds to maximize lipid yield while reducing solvent consumption and extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(75 citation statements)
references
References 29 publications
2
67
1
5
Order By: Relevance
“…It should be highlighted that degradation of sensitive biomolecules could occur during UAE by increase temperature or ultrasonic power. This has been observed in case of recovery of lipids from oleaginous Yarrowia lipolytica yeast for a biojetfuel application (Meullemiestre, Breil, Abert‐Vian, & Chemat, ) and oil from oleaginous seeds (Sicaire et al, ). In present study, temperature exhibited positive influence of polyphenols and antioxidant activity parameters (Figure ) suggesting that undesirable degradation of target compounds did not occur.…”
Section: Resultsmentioning
confidence: 77%
“…It should be highlighted that degradation of sensitive biomolecules could occur during UAE by increase temperature or ultrasonic power. This has been observed in case of recovery of lipids from oleaginous Yarrowia lipolytica yeast for a biojetfuel application (Meullemiestre, Breil, Abert‐Vian, & Chemat, ) and oil from oleaginous seeds (Sicaire et al, ). In present study, temperature exhibited positive influence of polyphenols and antioxidant activity parameters (Figure ) suggesting that undesirable degradation of target compounds did not occur.…”
Section: Resultsmentioning
confidence: 77%
“…The result of sample preparation is discussed and shown in Supporting Information, Fig. S3, S4, and Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…(6) were constructed. [36] For instance, Jiang et al, reported that ultrasound treatment considerably increased the primary oxidation and PV of the extracted oils. The high ultrasonic time especially at most levels of the cellulase concentration of 2% ( Figure 3A) and at most levels of the pH of 5.5 (Figure 3 B) increased the PV response of the extracted oil.…”
Section: Effect Of Process Variables On the Pv Responsementioning
confidence: 99%